Ownership Structure On Tax Avoidance: Empirical Study On Manufacturing Companies - Nurfadilah Yusri; Sri Wibawani Wahyuning Astuti; Dwi Irawan; Ahmad Juanda (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study aims to examine the effect of ownership structure as measured by institutional and public managerial ownership on tax avoidance. The population of this study are manufacturing companies listed on the IDX in 2019. The sampling technique uses a purposive sample which is a sampling method with criteria such as manufacturing companies listed on the IDX in 2019 and companies that present annual reports during 2019. The results show that managerial ownership structure affects tax avoidance, while public ownership structure and institutional ownership structure does not affect tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2019. These results indicate that companies owned by managers are more likely to carry out tax avoidance because managers have full power to prepare financial statements in accordance with their wishes compared to institutional and public ownership. This research contributes to providing information to stakeholders about which type of ownership structure is more likely to avoid tax.